Theoretical definition of legume grass seeds degree of extraction done by machine for seed extraction - M. V. Simonov; V. J. Mokiev (Аграрная наука Евро-Северо-Востока)
The study of the extraction machine was aimed at drawing analytical formulas which allow mathematically determine the quality indicators of the technological process. The object of this study is the process of grass seeds extraction. To achieve the aim, the before made scheme of operation of the similar devices and previously derived analytical dependencies were used, a number of assumptions were made and the process of extraction of grass seeds by their tangential motion in the workspace between the deck and the drum was studied. As a result of the research analytical dependences describing motion of particles of processed material in the extraction device of tangential type which allow to define degree of seeds extraction and to calculate the basic design parameters of the device at a design stage are offered. The conducted theoretical research and the analytical dependences obtained allowed to define with sufficient accuracy radius rb of a drum and frequency of rotation of nb of the extraction device of tangential type in dependence to the requirements for the degree of extraction of seeds provided by the device. For example, if the radius rb = 0.15 m, nb= 1250 min-1 the degree of extraction є is 95 %, in the experiment it is 95% with the same frequency of drum rotation. Mathematical models of the extraction device functioning and optimal design and technological parameters defined with their help can be used in the development of similar devices.